Development of a sensitive analytical method for the determination of cadmium using hydrogen assisted T-shape slotted quartz tube-atom trap-flame atomic absorption spectrophotometry - Sahin, Ipek; Buyukpinar, Cagdas; San, Nevim; Bakirdere, Sezgin (PERGAMON-ELSEVIER SCIENCE LTD, 2018)
Cadmium is an element that has several industrial applications and exposure to humans causes serious health problems. Hence, determination of this element in environmental samples surrounding humans is very crucial. In this study, a sensitive, accurate and inexpensive analytical method was developed for the determination of cadmium at trace levels. All the system parameters including acetylene flow rate, T-Shape Slotted Quartz Tube (T-SQT) height, sample flow rate, trapping period and hydrogen flow rate were optimized to obtain lower detection limits. Analytical performance of T-Shape Slotted Quartz Tube-Atom Trap-Flame Atomic Absorption Spectrophotometry (T-SQT-AT-FAAS) was determined under the optimum conditions, and the limit of detection (LOD) was calculated as 0.10 mu g L-1. The percent recovery of tap water samples spiked at 2.0, 3.0, 7.0 and 20 mu g L-1 were found to be between 99.5 and 102.8%. The %RSD values were all below 8.0%, indicating applicability and good accuracy of the method for the water matrix.
Keywords: Cadmium; Slotted quartz tube; Atom trap; Hydrogen; Atomic absorption; LIQUID-LIQUID MICROEXTRACTION; VAPOR GENERATION; SPECTROMETRY; LEAD; PRECONCENTRATION; BISMUTHINE; Spectroscopy